THE EVOLUTION OF CONSUMER BEHAVIOR IN THE COFFEE SHOP INDUSTRY - Adi Wahyu Anggara; Aryoga Wiweko (Faculty of Economics and Business | Universitas Diponegoro, 2026)
The global coffee shop industry has evolved from a transactional, caffeine-centred trade into a multidimensional experiential market, yet the consumer-behaviour literature documenting this shift remains fragmented across the marketing, hospitality, food-science, and sustainability disciplines. This study conducts a systematic literature review, following the PRISMA 2020 protocol, to map the thematic, theoretical, and methodological landscape of consumer-behaviour research in the coffee shop industry. A structured Scopus search covering 2015–2025, combined with multi-stage screening and a journal-quality threshold, yielded a final corpus of 51 empirical studies. Thematic synthesis identified six research streams: servicescape and service quality; experiential and cognitive-sensory processing; consumer-brand relationships and symbolic consumption; corporate social responsibility and sustainability; omni-channel and digital marketing; and disruptive technology and robot baristas. Methodologically, the field is dominated by cross-sectional survey designs analysed through structural equation modelling and is heavily concentrated in East and Southeast Asian contexts. The review surfaces three persistent frontiers: a satisfaction–loyalty decoupling, a sustainability intention–action gap, and an unresolved novelty effect in human–robot service interaction. The study contributes an integrated thematic map and a structured agenda emphasising behaviourally validated, longitudinal, and cross-cultural research designs.